Comparison of low and high pressure infiltration regimes on the density and highly porous microstructure of ceria ecoceramics made from sustainable cork templates - Novais, Rui M. (2019)
Cork templates were used to produce lightweight bulk biomimetic ecoceramic (environmentally conscious ceramic) monoliths. Bulk/monolithic ceramics are vital for many applications, i.e. energy materials and fuel cells. Using simple and flexible, aqueous green-chemistry procedures, for the first time the influence of infiltration regime, number of infiltration cycles and sintering temperature on ecoceramic density and microstructure was studied. This lightweight three-dimensionally ordered macroporous (3DOM) CeO2 preserved the hexagonal cellular structure of cork, but unlike the wood, the rear cell walls were open, greatly increasing open porosity. Higher sintering temperatures (1600 instead of 1000 °C) were required to produce cm size monolithic ecoceramics mechanically strong enough to be handled. The infiltration regime and number of infiltration cycles affected density and porosity. Lower infiltration pressure led to higher porosity ecoceramics (3.3–5.7%), which may favour catalytic performance, showing the possibility of tailoring porosity and specific surface area by modifying the number of infiltration cycles.